Neuro-fuzzy-based hand-off and opportunistic spectrum access for cognitive cooperative network - Kaiser, Moritz Shamim; Ahmed, Kazi Mohiuddin (© 2012 Inderscience Enterprises, 2016)
This article was published in the International Journal of Communication Networks and Distributed Systems [ © 2012 Inderscience Enterprises Ltd. ] and the definite version is available at :http://dx.doi.org/10.1504/IJCNDS.2012.046362. The Journal's website is at: http://www.inderscience.com/offer.php?id=46362